2010
DOI: 10.1175/2010jtecho734.1
|View full text |Cite
|
Sign up to set email alerts
|

Technology, Design, and Operation of an Autonomous Buoy System in the Western English Channel

Abstract: A buoy system has been developed to continually monitor the operationally demanding coastal and open-shelf environment of the western English Channel. The buoys measure a range of physical and biogeochemical parameters on an hourly basis at two established long-term monitoring sites and the data are relayed to shore in near–real time using radio communications. This paper describes the technological challenges faced in such long-term marine deployments including the mooring design, warning systems, command and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…The reliability rates of these monitoring stations are within the range of values reported for other buoy systems, which are 42% to 77% in the English Channel (Smyth et al 2010) and an average of 85% for the moored buoys of the National Buoy Data Center (Wilson 1987). The buoys have therefore proven to have a robust design, which allows the creation of an observation network and consequently a real-time monitoring system at the locations where the buoys are moored to measure variables ranging from water quality (turbidity, dissolved oxygen concentration, pigment concentration, pH, etc.)…”
Section: Resultssupporting
confidence: 69%
“…The reliability rates of these monitoring stations are within the range of values reported for other buoy systems, which are 42% to 77% in the English Channel (Smyth et al 2010) and an average of 85% for the moored buoys of the National Buoy Data Center (Wilson 1987). The buoys have therefore proven to have a robust design, which allows the creation of an observation network and consequently a real-time monitoring system at the locations where the buoys are moored to measure variables ranging from water quality (turbidity, dissolved oxygen concentration, pigment concentration, pH, etc.)…”
Section: Resultssupporting
confidence: 69%
“…Finding a position on the ship superstructure enabling a complete and unobstructed view of the sky as well as allowing access for periodic cleaning would almost certainly improve data quality. Multiple, season-long deployments (6-12 months) of the SPN1 on the Western Channel Observatory buoy at station L4 (Smyth et al, 2010) have shown the instrument to be remarkably resilient to such problems though, as it is always retrieved in a pristine condition. It is likely here that regular washing by rainwater keeps the dome free from fouling.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll concentration was determined for surface seawater by Turner fluorometry (Welshmeyer, 1994). Additionally, an autonomous buoy (Smyth et al, 2010b) positioned at L4 was equipped with sensors to record sea surface temperature (SST), salinity, wind speed and direction and optical properties such as Photosynthetically Active Radiation (PAR) and Ultra-Violet (UV) irradiance via a Satlantic hyperspectral radiometer. Net shortwave radiation was calculated as a function of date and position according to Smyth et al (2014).…”
Section: Sampling Site and Methodsmentioning
confidence: 99%